SOCIO-HYGIENIC ANALYSIS OF RISK FACTORS IN PATIENTS WITH DISEASES OF THE ENDOCRINE SYSTEM - Nizom J. Ermatov; Nodir K. Khaydarov; Ikhtiyor U. Abdulkhakov; Anvar N. Shukurov; Bobomurod B. Ortikov (Central Asian Journal of Medicine, 2023)
The study was conducted among 1375 (726 men and 649 women) patients aged 18-69 living in rural and urban areas of the Bukhara region, registered in the Bukhara Endocrinological Dispensary. Questionnaire data collected from patients evaluated using the “case-control” method. The risk factor with the greatest impact on health status is malnutrition (OR-15.6; 95% CI 12.9-18.8). As risk factors, not only low fruit consumption, but also the consumption of citrus fruits with allergenic properties the odds ratio was 12.6. In cases of high consumption of sweets, the odds ratio was 10.5 (from 8.7 to 12, 5), in addition, in cases of insomnia and heavy physical work, the odds ratio was 2.0. The results shows that the main part of the risk factors for the disease is associated with nutrition.